Corporate Governance and Firm Value: The Impact of Corporate Social Responsibility - Jo, Hoje; Harjoto, Maretno A. (2011)
This study investigates the effects of internal and external corporate governance and monitoring mechanisms on the choice of corporate social responsibility (CSR) engagement and the value of firms engaging in CSR activities. The study finds the CSR choice is positively associated with the internal and external corporate governance and monitoring mechanisms, including board leadership, board independence, institutional ownership, analyst following, and anti- takeover provisions, after controlling for various firm characteristics. After correcting for endogeneity and simultaneity issues, the results show that CSR engagement positively influences firm value measured by industry-adjusted Tobin’s q. We find that the impact of analyst following for firms that engage in CSR on firm value is strongly positive, while the board leadership, board independence, blockholders’ ownership, and institutional ownership play a relatively weaker role in enhancing firm value. Furthermore, we find that CSR activities that address internal social enhancement within the firm, such as employees diversity, firm relationship with its employees, and product quality, enhance the value of firm more than other CSR subcategories for broader external social enhancement such as community relation and environmental concerns.
Keywords: M14; L2; G34; Firm value; analyst following; Corporate Governance; Corporate Social Responsibility